Imagining online research design: Is it connective case study or virtual ethnography? - Grace Pigozzi (Digital Culture & Education, 2017)
Conducting research online that focuses on various writing genres with adolescent authors demands imagination and improvisation as their composition meanders across multiple communities, forums, and expressive modes, while it simultaneously ignores boundaries and creates new spaces. Research of online contexts is crucial as technology plays an increasing role in education policy (CCSSO/NGA, 2010). As unique windows to adolescent online writing, affinity spaces as semiotic spaces are nested between competing cultural entities in which cultural identities across differences of class, gender roles, and values are negotiated (Bhatt, 2008). Affinity spaces have the capacity to create new structures of sociolinguistic and semiotic authority as they redefine approaches to disciplinary learning, and group and individual identity. It is within the discursive spaces of online out-of-school writing that educators can strive to cultivate a similar classroom space for explicit instruction in formal writing. This paper from a study of adolescent writers in an urban Midwestern literacy center compares and contrasts appropriate methods for inquiry as it explores the instructional potential of blogging to engage students more authentically and dialogically than long-established pedagogical practices.